The structure and compound of composite based on Ni and ultradispersed diamonds - Довбій, Тетяна Анатоліївна (Technology audit and production reserves, 2012)
The article describes the results of the study of obtaining a composite material based on nickel and ultradispersed Diamond by chemical reduction of Ni from amorphous precipitate of nickel carbonate/hydroxide. The results of study of structure and compound of nickel composite are presented